KI 2016: Advances in Artificial Intelligence 39th Annual German Conference on AI, Klagenfurt, Austria, September 26-30, 2016, Proceedings - Friedrich, Gerhard; Helmert, Malte; Wotawa, Franz (Lecture Notes in Artificial Intelligence,, 2016)
This book constitutes the refereed proceedings of the 39th Annual German Conference on Artificial Intelligence, KI 2016, in conjunction with the Österreichische Gesellschaft für Artificial Intelligence, ÖGAI, held in Klagenfurt, Austria, in September 2016. The 8 revised full technical papers presented together with 12 technical communications, and 16 extended abstracts were carefully reviewed and selected from 44 submissions. The conference provides the opportunity to present a wider range of results and ideas that are of interest to the KI audience, including reports about recent own publications, position papers, and previews of ongoing work.